The SGLT2 inhibitor dapagliflozin in heart failure with preserved ejection fraction: a multicenter randomized trial - Nassif, Michael E.; Windsor, Sheryl L.; Borlaug, Barry A.; Kitzman, Dalane W.; Shah, Sanjiv J.; Tang, Fengming; Khariton, Yevgeniy; Malik, Ali O.; Khumri, Taiyeb; Umpierrez, Guillermo; Lamba, Sumant; Sharma, Kavita; et al. (Nature medicine, 2021)
Patients with heart failure and preserved ejection fraction (HFpEF) have a high burden of symptoms and functional limitations, and have a poor quality of life. By targeting cardiometabolic abmormalities, sodium glucose cotransporter 2 (SGLT2) inhibitors may improve these impairments. In this multicenter, randomized trial of patients with HFpEF (NCT03030235), we evaluated whether the SGLT2 inhibitor dapagliflozin improves the primary endpoint of Kansas City Cardiomyopathy Questionnaire Clinical Summary Score (KCCQ-CS), a measure of heart failure-related health status, at 12 weeks after treatment initiation. Secondary endpoints included the 6-minute walk test (6MWT), KCCQ Overall Summary Score (KCCQ-OS), clinically meaningful changes in KCCQ-CS and -OS, and changes in weight, natriuretic peptides, glycated hemoglobin and systolic blood pressure. In total, 324 patients were randomized to dapagliflozin or placebo. Dapagliflozin improved KCCQ-CS (effect size, 5.8 points (95% confidence interval (CI) 2.3–9.2, P = 0.001), meeting the predefined primary endpoint, due to improvements in both KCCQ total symptom score (KCCQ-TS) (5.8 points (95% CI 2.0–9.6, P = 0.003)) and physical limitations scores (5.3 points (95% CI 0.7–10.0, P = 0.026)). Dapagliflozin also improved 6MWT (mean effect size of 20.1 m (95% CI 5.6–34.7, P = 0.007)), KCCQ-OS (4.5 points (95% CI 1.1–7.8, P = 0.009)), proportion of participants with 5-point or greater improvements in KCCQ-OS (odds ratio (OR) = 1.73 (95% CI 1.05–2.85, P = 0.03)) and reduced weight (mean effect size, 0.72 kg (95% CI 0.01–1.42, P = 0.046)). There were no significant differences in other secondary endpoints. Adverse events were similar between dapagliflozin and placebo (44 (27.2%) versus 38 (23.5%) patients, respectively). These results indicate that 12 weeks of dapagliflozin treatment significantly improved patient-reported symptoms, physical limitations and exercise function and was well tolerated in chronic HFpEF. In a multicenter, randomized trial, the SGLT2 inhibitor dapagliflozin improved the health status and exercise function of patients with heart failure with preserved ejection fraction (HFpEF), a condition for which effective treatments are lacking.